ANALISIS GCG KOMPENSASI RUGI FISKAL PERTUMBUHAN PENJUALAN INTENSITAS MODAL TERHADAP PENGHINDARAN PAJAK PERUSAHAAN MANUFAKTUR DI BEI - Yuliana; Poniman (LPPM Universitas Putera Batam, 2022)
The level of tax revenue is very important as an indicator of the independence of a nation's development. Tax is one of the primary assets of state revenue from within the country to fund the State Revenue and Expenditure Budget. Tax revenue is often not achieved due to tax avoidance practices. The phenomenon of tax avoidance in Indonesiamay be seen from the ratio of country taxes. This study ambitions to decide the impact of GCG, Fiscal Loss Compensation, Sales Growth, Capital Intensity on Tax Avoidance of Manufacturing Companies on the IDX. The population used consisted of 59 companies with purposive sampling technique, the sample consisted of 40 data from 8 companies. The data is taken using secondary data taken from the official website www.idx.co.id and processed using the SPSS version 25 application. Based totally on those outcomes, it is stated that the independent board of commissioners has no partial effect on tax avoidance, institutional ownership has a partial effect on tax avoidance , fiscal loss compensation has no partial effect on tax avoidance, sales growth does not partially affect tax avoidance, capital intensity does not partially affect tax avoidance of manufacturing companies listed on the Indonesia Stock Exchange.